2019
DOI: 10.21276/ijcmsr.2019.4.2.29
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Palpable Breast Lumps by Digital Breast Tomosynthesis and MRI Breast with its Histopathological Correlation

Abstract: Breast cancer is the leading cause of mortality and morbidity in females worldwide. Combating this, needs early detection of malignancy and prompt management. Various modalities available are-digital mammography +/tomosynthesis (DBT), ultrasound with colour Doppler and elastography, dynamic contrast enhanced MRI (DCE-MRI) with MRI being considered as the best. This study was done to compare efficacy of digital breast tomosynthesis and MRI breast in evaluation of palpable breast masses and other suspicious brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
1
3
2
Order By: Relevance
“…The sensitivity of DBT and DBT + USG were equivalent, which was 88.89%, whereas it was 100% on MRI. Our finding was comparable to several studies which reported sensitivity of DBT ranging from 90–93% with sensitivity of MRI near 100% [ 9 , 10 , 11 ]. In a study done by Kamal et al, in which they assessed the ability of DBT and MRI in improving the sensitivity of digital mammography, they noted that DBT alone had equal sensitivity compared to MRI, which was 92% [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The sensitivity of DBT and DBT + USG were equivalent, which was 88.89%, whereas it was 100% on MRI. Our finding was comparable to several studies which reported sensitivity of DBT ranging from 90–93% with sensitivity of MRI near 100% [ 9 , 10 , 11 ]. In a study done by Kamal et al, in which they assessed the ability of DBT and MRI in improving the sensitivity of digital mammography, they noted that DBT alone had equal sensitivity compared to MRI, which was 92% [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…The PPV of all three modalities in our study were generally lower, which were 66.7% for DBT, 72.7% for DBT + USG and 64.3% for MRI, as compared to other literature review, i.e., 80.6–85.7% for DBT, 82.8% for DBT + USG and 71.1–96.6% for MRI [ 8 , 10 , 24 ]. This was likely due to the nature of lesion categorization in our study, i.e., BI-RADS 3 was categorized as malignant.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations